2009
DOI: 10.1086/595986
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Capacity for Gastrointestinal Colonization inEnterococcus faeciumin a Mouse Model

Abstract: A high level of gastrointestinal colonization frequently precedes invasive infection due to Enterococcus faecium. Factors other than antimicrobial resistance that promote gastrointestinal colonization by E. faecium have not been identified. We tested the ability of a colonization-proficient clinical E. faecium isolate (C68) to transfer colonizing ability to noncolonizing E. faecium recipient strains. Transconjugants derived from matings that used E. faecium D344SRF as a recipient strain colonized mouse gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 23 publications
(37 reference statements)
2
55
0
7
Order By: Relevance
“…The other fms genes were also frequently present at rates ranging from 67% to 97% in the VREfm isolates. The esp Efm and hyl Efm genes, which have previously been associated with CC17 (28,38), were detected in South American VR E. faecium isolates (69% and 23% of isolates, respectively). (29) 48 (14) 48 (14) 93 (27) (17) 29 (5) 29 (5) 59 (10) 0 (0) 0 (0) 88 (15) 47 (8) 41 (7) Venezuela (24) 25 (6) 25 (6) 58 (14) 4 (1) (7) 14 (1) 0 (0) 43 (3) 14 (1) 0 (0) 14 (1) 28 (2) 28 (2) Ecuador (9) 22 (2) …”
Section: Phenotypic Characteristics Of Enterococcal Isolates From Thementioning
confidence: 85%
See 2 more Smart Citations
“…The other fms genes were also frequently present at rates ranging from 67% to 97% in the VREfm isolates. The esp Efm and hyl Efm genes, which have previously been associated with CC17 (28,38), were detected in South American VR E. faecium isolates (69% and 23% of isolates, respectively). (29) 48 (14) 48 (14) 93 (27) (17) 29 (5) 29 (5) 59 (10) 0 (0) 0 (0) 88 (15) 47 (8) 41 (7) Venezuela (24) 25 (6) 25 (6) 58 (14) 4 (1) (7) 14 (1) 0 (0) 43 (3) 14 (1) 0 (0) 14 (1) 28 (2) 28 (2) Ecuador (9) 22 (2) …”
Section: Phenotypic Characteristics Of Enterococcal Isolates From Thementioning
confidence: 85%
“…It was previously shown that hospital-associated E. faecium isolates from diverse geographical locations carry large, transferable plasmids containing the hyl Efm gene (which encodes a putative family 84 glycosyl hydrolase enzyme) that, additionally, are associated with vancomycin and aminoglycoside resistance genes (4). These hyl Efm -containing plasmids have emerged as important virulence and colonization determinants of CC17 of E. faecium (4,28). More recently, one of the fms clusters (fms20-fms21 [pilA]) encoding pilus-like proteins was also found to be located in a large hyl Efm -carrying plasmid in U.S. strain TX0016 (strain DO) (17).…”
Section: Phenotypic Characteristics Of Enterococcal Isolates From Thementioning
confidence: 99%
See 1 more Smart Citation
“…Strains from the community-associated clade almost never have very large plasmids containing a hyl-like gene, while hospital-associated strains often (~ 30 % in one study) harbour this gene (Rice et al, 2003). These hyl plasmids have been shown to increase colonisation of mice GI tracts and to increase lethality in a murine peritonitis model and, thus, might contribute to the success of at least some members of the hospital-associated clade (Rice et al, 2009;Panesso et al, 2011).…”
Section: Hyl-like Genementioning
confidence: 98%
“…At present, within the Enterococcus genus, E. faecium has emerged as the most therapeutically challenging organism. C68 readily colonizes the mouse gastrointestinal tract under antimicrobial selective pressure (Rice et al, 2009). Its genome has been completely sequenced (Lam et al, 2012).…”
Section: Enterococcus Faecium C68mentioning
confidence: 99%